2016
DOI: 10.1515/icom-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Serious Gaming in Augmented Reality using HMDs for Assessment of Upper Extremity Motor Dysfunctions

Abstract: For a better understanding of how different disorders affect motor function, a uniform, standardized and objective evaluation is a desirable goal for the clinical community. We explore the potential of Augmented Reality (AR) combined with serious gaming and free hand tracking to facilitate objective, cost-effective and patient-friendly methods for evaluation of upper extremity motor dysfunction in different patient groups. In this paper, we describe the design process of the game and the system architecture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Previous studies on technology assistance for rehabilitation and health and fitness can be classified in terms of the used technology and hardware, which range from the application of professional tracking hardware [ 38 ] over virtual and augmented reality HMDs (head mounted displays) [ 39 ] and mainstream gaming hardware [ 40 ] to everyday mobile phones [ 41 - 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on technology assistance for rehabilitation and health and fitness can be classified in terms of the used technology and hardware, which range from the application of professional tracking hardware [ 38 ] over virtual and augmented reality HMDs (head mounted displays) [ 39 ] and mainstream gaming hardware [ 40 ] to everyday mobile phones [ 41 - 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Augmented reality (AR) systems with HMDs (such as the Microsoft HoloLens) allow to graphically overlay the visual perception with additional information, which would be well-suited to provide patients with feedback on exercise performance. The design of AR games for upper extremity motor dysfunctions was investigated [ 47 ] and in a follow-up study, an AR game for an HMD system was evaluated [ 39 ]. However, as compared with a mobile phone, AR HMDs are expensive and not widely available at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the consultation of 1 clinician, 1 movement scientist and 7 PD patients, we designed the game "post office trouble" [7] which focuses on a simple but functional task, i.e., reaching and grasping an object. The game puts a player in the position of a post office worker who has to sort packages, thereby making as few mistakes as possible.…”
Section: Task Designmentioning
confidence: 99%
“…Based on the consultation of 1 clinician, 1 movement scientist and 7 Parkinson's Disease (PD) patients, we designed the game "post office trouble" [6] which focuses on a simple but functional task, i.e., reaching and grasping an object. The game puts the player in the position of a post office worker who has to sort international packages while making as few mistakes as possible.…”
Section: User Studiesmentioning
confidence: 99%
“…A study on engagement and usability with 8 healthy elderly participants showed that the usability of the game is still quite low, but that there is potential for engagement [6]. Following experiments with healthy users [8], [16], we conducted a study that specifically explored the usability and engagement of different puzzle types (colors/images), interaction modalities (grasping/pointing) and presence of visual feedback of virtual hand (yes/no) in augmented reality.…”
Section: User Studiesmentioning
confidence: 99%